Influence of plasma processing on recovery and analysis of circulating nucleic acids. - Karen Page; David S Guttery; Nathalie Zahra; Lindsay Primrose; Shona R Elshaw; J Howard Pringle; Kevin Blighe; Stephanie D Marchese; Allison Hills; Laura Woodley; Justin Stebbing; R Charles Coombes; et al. (PLoS ONE)
Circulating nucleic acids (CNAs) are under investigation as a liquid biopsy in cancer. However there is wide variation in blood processing and methods for isolation of circulating free DNA (cfDNA) and microRNAs (miRNAs). Here we compare the extraction efficiency and reproducibility of 4 commercially available kits for cfDNA and 3 for miRNA using spike-in of reference templates. We also compare the effects of increasing time between venepuncture and centrifugation and differential centrifugation force on recovery of CNAs. cfDNA was quantified by TaqMan qPCR and targeted deep sequencing. miRNA profiles were assessed with TaqMan low-density arrays and assays. The QIAamp(®) DNA Blood Mini and Circulating nucleic acid kits gave the highest recovery of cfDNA and efficient recovery (>90%) of a 564bp spike-in. Moreover, targeted sequencing revealed overlapping cfDNA profiles and variant depth, including detection of HER2 gene amplification, using the Ion AmpliSeq™Cancer Hotspot Panel v2. Highest yields of miRNA and the synthetic Arabidopsis thaliana miR-159a spike-in were obtained using the miRNeasy Serum/Plasma kit, with saturation above 200 µl of plasma. miRNA profiles showed significant variation with increasing time before centrifugation (p<0.001) and increasing centrifugation force, with depletion of platelet associated miRNAs, whereas cfDNA was unaffected. However, sample replicates showed excellent reproducibility on TaqMan low density arrays (ρ = 0.96, p<0.0001). We also successfully generated miRNA profiles for plasma samples stored > 12 years, highlighting the potential for analysis of stored sample biobanks. In the era of the liquid biopsy, standardisation of methods is required to minimise variation, particularly for miRNA.